2013
DOI: 10.3389/fpsyt.2013.00052
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Activity in Neuropsychiatric Disorders

Abstract: N-Methyl-d-aspartate (NMDA) receptors play a variety of physiologic roles and their proper signaling is essential for cellular homeostasis. Any disruption in this pathway, leading to either enhanced or decreased activity, may result in the manifestation of neuropsychiatric pathologies such as schizophrenia, mood disorders, substance induced psychosis, Huntington’s disease, Alzheimer’s disease, and neuropsychiatric systemic lupus erythematosus. Here, we explore the notion that the overlap in activity of at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 63 publications
2
85
0
4
Order By: Relevance
“…N ‐methyl‐ d ‐aspartate receptors (NMDAR) are well known to be associated with psychiatric disorders (Lakhan, Caro, & Hadzimichalis, 2013). With no surprise, they were also linked to ASD risk (Lee, Choi, & Kim, 2015).…”
Section: Reviewmentioning
confidence: 99%
“…N ‐methyl‐ d ‐aspartate receptors (NMDAR) are well known to be associated with psychiatric disorders (Lakhan, Caro, & Hadzimichalis, 2013). With no surprise, they were also linked to ASD risk (Lee, Choi, & Kim, 2015).…”
Section: Reviewmentioning
confidence: 99%
“…NMDA receptor also plays a key role in the formation of neuronal circuits. Evidences indicated that NMDA receptor is vital for learning and memory (Lakhan et al, 2013;Li and Tsien, 2009). Researches show that there is also a certain relationship between gut microbiota and NMDA receptor expression.…”
Section: The Influence Of Gut Microbiota On Neurochemical and Metabolmentioning
confidence: 99%
“…Adicionalmente, un brote previo de psicosis inducida por un fármaco antituberculoso aumenta el riesgo de padecerla con otro medicamento antimicobacteriano (4,6). En el caso que discutimos, es relevante el largo tiempo previo de consumo de alcohol, marihuana y pasta básica de cocaína por nuestro paciente: los cambios neurobiológicos que acarrea la dependencia a estas sustancias psicoactivas, con alteraciones en la sensibilidad de los receptores de glutamato y dopamina, legítimamente deben considerarse como probables factores implicados en el desarrollo de la sintomatología psicótica en el presente ejemplo (8).…”
Section: Discussionunclassified
“…Dado que el receptor NMDA de glutamato desempeña un rol general en la regulación de transducción de señales en múltiples regiones del cerebro (con presencia prominente de receptores postsinápticos NMDA en las estructuras límbicas) cualquier alteración de su funcionamiento puede redundar en una gran variedad de patologías neuropsiquiátricas: desde la isquemia cerebral a la epilepsia, pasando por diversas enfermedades neurodegenerativas, la esquizofrenia, varios trastornos de ansiedad y el dolor neuropático (8). No se ha dilucidado plenamente aún el mecanismo fisiopatológico por el cual la cicloserina contribuye a la emergencia de síntomas psicóticos en determinados individuos.…”
Section: Discussionunclassified